2020
DOI: 10.1080/17483107.2020.1738566
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to using assistive technology among students with visual disability in schools for the blind in Delhi, India

Abstract: Background: Students with visual loss may benefit from assistive technology (AT) for their educational activities. Aim: To understand the barriers faced in using ATs by students who have heard of ATs and reported needing them but were not using them (acquainted students), at schools for the blind in Delhi.Methods: Two hundred and fifty students were selected randomly from ten schools for the blind in Delhi and screened for presenting and pinhole binocular distance vision using a modified 'E' chart and multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…As reported by [10] it is estimated that at least 2.2 billion people in the world have visual impairment including low vision. Furthermore, [11] also reveals that the number of visually impaired people in low-income countries and middle-income countries is four times higher than in high-income countries.…”
Section: The Current State Of Newly Registered Persons With Disabilities (Pwds)mentioning
confidence: 97%
See 3 more Smart Citations
“…As reported by [10] it is estimated that at least 2.2 billion people in the world have visual impairment including low vision. Furthermore, [11] also reveals that the number of visually impaired people in low-income countries and middle-income countries is four times higher than in high-income countries.…”
Section: The Current State Of Newly Registered Persons With Disabilities (Pwds)mentioning
confidence: 97%
“…Currently, around 10% of the world's population or roughly 650 million people have some form of disability in which most of them live in developing countries [10]. Moreover, as estimated by the World Bank, 20% of the world's poorest people have some form of disability and tend to be regarded in their communities as the worst people [11]. In each of these years, it is estimated that over 1 million children with disabilities were born and unfortunately 90% of them do not attend school, particularly those who live in developing countries [10].…”
Section: The Current State Of Newly Registered Persons With Disabilities (Pwds)mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 16 ] Despite the well-known benefits of ATVI, studies in India have reported poor availability of ATVI in blind schools. [ 17 ] For example, a study reported that only Braille slate, stylus, and abacus were assistive devices available at most of the blind schools (>90%). The same study reported that 11 of 52 ATVIs included in the study were available in 60% of the blind schools in Delhi with few AT trainers in these schools.…”
mentioning
confidence: 99%